Świat we wszystkich swoich częściach… Władysława Aleksandra Łubieńskiego jako źródło do poznania Ameryki Łacińskiej w latach 40. XVIII wieku - Szylar, Anna (Biuletyn Historii Wychowania, 2026)
W.A. Łubieński’s book entitled „The World in All Its Parts” was published in 1740. It is the first world geography published in Polish. The author included a description of countries and territories located in Europe, Asia, Africa, North America and South America. The article uses a description of the Western Hemisphere regarding South and Central America. The description is geographical and historical in nature. The article is divided into several parts. The introduction discusses the sources of information about Latin America in the Republic of Poland until the publication of the book by W.A. Łubieński. Then the author and the motives for writing the book are presented and the source material is characterized. The last part is a description of Latin America. It is divided into the following topics: ancient accounts of the existence of an unknown land, the discovery of America, the location and geographical conditions, fauna and flora, the culture of peoples in the pre- and post Cumbrian period, the colonization of the West Indies and the system of managing colonies, the Catholic Church and faith. W.A. Łubieński’s work published in 1740 satisfied the inner curiosity and the need for science. This work was the basis for fundamental changes in Polish science, education, periodicals, printing of textbooks and scientific works.